(untitled) (Research, Society and Development, 2020)
Objective: To analyze inequalities in access to medicines in Brazil. Methodology: A cross-sectional study was conducted with individuals over 18 years of age, who analyzed the prescription of the drugs prescribed in the last health care based on data from the National Health Survey 2013. The prevalence of access to medicines was described according to demographic, socioeconomic and access to health services. The data were presented from proportions values and 95% confidence interval. The analysis of the significance between the data was evaluated from the intercession of the confidence intervals. Results: From the study population, most of the subjects were able to obtain all medications. The proportion of people who obtained all medications was higher among residents of Espírito Santo; individuals aged 18 to 29 years, white in color and with complete higher education. Part of the individuals had as source of obtaining the public service. The reason most often cited by residents for not getting all prescription drugs was that the drug was not available at the health facility. Conclusion: There were extreme inequalities in access to medicines in Brazil, pointing to the need for policies that increase access to medicines.